2014
DOI: 10.1039/c3gc41458b
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient SO2capture by phenyl-containing azole-based ionic liquids through multiple-site interactions

Abstract: Ionic liquids are suitable for the absorption of acid gases such as SO 2 because of their unique properties.In this work, a new method was developed for the highly efficient capture of SO 2 by introducing a phenyl group into the azole-based ionic liquids. It was found that these phenyl-containing azole-based ionic liquids reacted with SO 2 through multiple-site interactions between the anion and SO 2 , resulting in an extremely high SO 2 capacity of up to ∼5.7 mole per mole ionic liquid. Spectroscopic investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
77
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 54 publications
7
77
0
Order By: Relevance
“…The interaction of SO 3 2− and SO 4 2− at the amine site occurred primarily by the NH−H···OSO (hydrogen bonding) indicated by the shift in IR intensity for the symmetric ν s (N−H) vibration from 3650 to 3389 cm −1 for SO 3 2− (Figure 4d) and to 3380 cm −1 for SO 4 2− (Figure 4e). The optimized structures for the SO 3 -[diamine], and the SO 4 -[diamine] molecules produced IR intensities for the ν s (SO) vibrations at 981 and 1014 cm −1 for the SO 3 2− adsorbed species and at 1151 and 1205 cm −1 for the SO 4 2− adsorbed species, as shown in Table 2.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The interaction of SO 3 2− and SO 4 2− at the amine site occurred primarily by the NH−H···OSO (hydrogen bonding) indicated by the shift in IR intensity for the symmetric ν s (N−H) vibration from 3650 to 3389 cm −1 for SO 3 2− (Figure 4d) and to 3380 cm −1 for SO 4 2− (Figure 4e). The optimized structures for the SO 3 -[diamine], and the SO 4 -[diamine] molecules produced IR intensities for the ν s (SO) vibrations at 981 and 1014 cm −1 for the SO 3 2− adsorbed species and at 1151 and 1205 cm −1 for the SO 4 2− adsorbed species, as shown in Table 2.…”
Section: Introductionmentioning
confidence: 91%
“…The interaction of SO 3 2− and SO 4 2− at the amine site occurred primarily by the NH−H···OSO (hydrogen bonding) indicated by the shift in IR intensity for the symmetric ν s (N−H) vibration from 3650 to 3389 cm −1 for SO 3 2− (Figure 4d) and to 3380 cm −1 for SO 4 2− (Figure 4e). The optimized structures for the SO 3 -[diamine], and the SO 4 -[diamine] molecules produced IR intensities for the ν s (SO) vibrations at 981 and 1014 cm −1 for the SO 3 2− adsorbed species and at 1151 and 1205 cm −1 for the SO 4 2− adsorbed species, as shown in Table 2. Comparison of the simulated spectra to the difference IR spectra collected by ATR-IR ( Figure 4f) and DRIFTS (Figure 4g), the experimental IR data show the formation of the sulfite (1009 and 978 cm −1 ) and the sulfate (1041, 1077, 1144, and 1176 Figure 5 (panels a and b) show the ATR-IR difference spectra during SO 2 adsorption at 50°C for cycle no.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…To develop a new process based on ILs for gas separation, taking SO 2 as an example, a number of efforts have been spent in designing the novel functionalized ILs for higher absorption capacity of SO 2 and lower absorption enthalpy, and studying the mechanism between SO 2 and ILs by experimental methods and simulation calculations [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Nevertheless, although the available studies on different aspects of ILs have increased almost exponentially, understanding deeply the physical properties of ILs is still a major point of discussion, which is essential for the design and scale-up of chemical processes in their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Anion functionalization is an important method to design and achieve the task-specific ILs. Recently, azole-based anion functionalized ILs have been widely used as the basic catalyst in the organic reaction [5][6][7], as the extraction in the separation process [8,9], and as the absorbent in the acidic gas absorption process [10][11][12][13][14][15]. For example, the imidazolide anion functionalized protic IL ([HMTBD]IM) was prepared by Wang et al through the neutralization reaction of 7-meth yl-1,5,7-triazabicyclo [4.4.0]dec-5-ene (MTBD) and imidazole to capture CO 2 , and the results showed that [HMTBD]IM was capable of rapid and reversible capture of about one equivalent of CO 2 due to the reactivity of the imidazolide anion to CO 2 [12].…”
Section: Introductionmentioning
confidence: 99%